IMPEMENTASI METODE WEB ENGINEERING DALAM MEMBANGUN SISTEM INFORMASI AKADEMIK SEKOLAH BERBASIS WEB - Helda Yudiastuti (IST AKPRIND Yogyakarta, 2018)
Development of current computer technology to speed the process has enabled the development of computer-based information systems. This study discusses the creation of academic Web applications subjected to a secondary vocational school, considering the quality of the processing of the data used is still a manual that is still using paper and a pen. The methods used to design this academic information system is a method of web engineering, Web Engineering is a process that is used to create a system of web-based applications by using the science of engineering, principles of management and systematic approach so that the system can be obtained and web applications with high quality. include Activities Formulation, Planning, Analysis, Engineering, Page Generation and Testing, with academic information system design of establishing a web-based it can improve the quality of academic data processing at that school. The design of this application using PHP and MySQL. System testing done by adjusting the entire needs that have been defined previously with the created function. The existence of this school's academic information systems, It is hoped that it can help and facilitate the processing of school academic data with maximum and practical because it can be accessed anywhere while keeping the data safe which was previously done manually and data is easily lost. With the existence of academic information system is expected that the deficiencies that have occurred can be overcome and the process of presenting the report can be done quickly and accurately. So that the service to students, teachers and principals will be more leverage.